Approaches to Monitoring and Evaluation Strategy Development - Dumitru, Adina; Garcia, Igone; Zorita, Saioa; Tomé-Lourido, Davidé; Cardinali, Marcel; Feliu, E.; Fermoso, J.; Ferilli, G.; Guidolotti, G.; Hölscher, K.; Lodder, M.; Reichborn-Kjennerud, K.; et al. (Evaluating the impact of nature-based solutions. A handbook for practitioners)
The Handbook aims to provide decision-makers with a comprehensive NBS impact assessment framework, and a robust set of indicators and methodologies to assess impacts of nature-based solutions across 12 societal challenge areas: Climate Resilience; Water Management; Natural and Climate Hazards; Green Space Management; Biodiversity; Air Quality; Place Regeneration; Knowledge and Social Capacity Building for Sustainable Urban Transformation; Participatory Planning and Governance; Social Justice and Social Cohesion; Health and Well-being; New Economic Opportunities and Green Jobs. Indicators have been developed collaboratively by representatives of 17 individual EU-funded NBS projects and collaborating institutions such as the EEA and JRC, as part of the European Taskforce for NBS Impact Assessment, with the four-fold objective of: serving as a reference for relevant EU policies and activities; orient urban practitioners in developing robust impact evaluation frameworks for nature-based solutions at different scales; expand upon the pioneering work of the EKLIPSE framework by providing a comprehensive set of indicators and methodologies; and build the European evidence base regarding NBS impacts. They reflect the state of the art in current scientific research on impacts of nature-based solutions and valid and standardized methods of assessment, as well as the state of play in urban implementation of evaluation frameworks.
Keywords: atmospheric pollution; biodiversity; community resilience; database; decision-making; environmental impact; environmental indicator; environmental risk prevention; innovation; natural hazard; sustainable development; urban area; user guide; waste management